(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, the linguistic units present in the language are analyzed based on sources in English and Uzbek languages. Phrases related to human nature and character and their characteristics are considered within the framework of phraseosemantic field from semantic, grammatical, etymological and stylistic aspects. In the concluding part, the scope of use and study of phraseological units are highlighted as national values and people’s experience.